Joropo Brand - Erika Baquero - Ángela Tovar - Guillermo Quiñonez - Jennifer Vega (GEON Journal (Management, Organizations and Business), 2015)
This paper presents some progress on research, whereby the possibility of creating a brand that represents the Ranger folklore abroad is evaluated. The overall objective of the research was to identify attributes and factors that must Ranger potentiate folklore, so that in the future as a basis for internationalization through a brand. The methodology was a mixed approach, in order to get a broader and deeper picture. The research "Brand Joropo" was subject to theories of internationalization brand and burrowing folklore. As for internationalization it was decided to implement the eclectic theory and the Uppsala model, as it is intended to apply the theory of Born Global to the desired mark. On the other hand, the concept most suitable brand, is posed by Kevin Roberts in his book Lovemarks (2005), as it relates to burrowing folklore worked with Ranger's book Folklore, Miguel Angel Martin (2000)
Keywords: Joropo; Plains Folklore; Brand; Internationalization